Nonalcoholic fatty liver was associated with asymptomatic gallstones in a Chinese population. Issue 38 (September 2017) - Qiao, Qiao-Hua; Zhu, Wen-Hua; Yu, Yun-Xian; Huang, Fei-Fei; Chen, Li-Ying
Abstract : Abstract: The aim of this study was to determine the association between nonalcoholic fatty liver disease (NAFLD) and asymptomatic gallstones in a Chinese population. The study had a cross-sectional design and enrolled 7583 subjects who visited the physical check-up center at Sir Run Run Shaw Hospital between 2009 and 2011. Colorimetric methods were used to measure the levels of cholesterol, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), whereas fasting plasma glucose (FPG) level was measured using a dextrose-oxidizing enzyme method. Subjects who completed a questionnaire and underwent a medical and ultrasound examinations were included in the study. The prevalence of NAFLD was significantly higher in patients with asymptomatic gallstones than in those without asymptomatic gallstones (58.98% vs 46.58%, respectively; P  < .0001). The age-adjusted odds ratio (OR) for NAFLD being accompanied by asymptomatic gallstones was 1.35 [95% confidence interval (CI), 1.13–1.61; P  = .0009] in male and 1.92 (95% CI, 1.45–2.54; P  < .0001) in female subjects. Asymptomatic gallstones were associated with NAFLD in subjects aged < 50 years (OR = 1.74, 95% CI, 1.44–2.12; P  < .0001), but not in subjects aged > 50 years (OR = 1.17, 95% CI, 0.92–1.48; P  = .2040). The OR of NAFLD for asymptomatic gallstones was 1.28 after multivariate logistic regression analysis (95% CI, 1.07–1.52; P  = .006). Our results indicated that asymptomatic gallstones are strongly associated with NAFLD in the Chinese study population.